Bladder Pain Syndrome (Interstitial Cystitis) Consensus 2019: The Report of the Turkish Continence Society Bladder Pain Syndrome/Interstitial Cystitis Working Group - (:unkn) unknown (GALENOS YAYINCILIK, 2020)
Bladder pain syndrome is an important chronic pain syndrome which seriously reduces the patients' quality of life. It is a diagnosis of exclusion. It is defined as a clinical diagnosis composed of chronic (>6 months) pain/pressure/discomfort that is primarly perceived from the bladder and/or pelvis, and accompanied by urgency and/or frequency of urination. Throughout this paper, the definition, characteristic features, diagnostic tests and attempts, interpretation of the findings and the different treatment algorithms suggested by different organizations will be discussed.
Keywords: Bladder Pain syndrome; Interstitial cystitis; Chronic pelvic pain; PENTOSAN POLYSULFATE SODIUM; INTRAVESICAL HYALURONIC-ACID; DOUBLE-BLIND; CHONDROITIN SULFATE; ALKALINIZED LIDOCAINE; SJOGRENS-SYNDROME; VEHICLE CONTROL; SYMPTOMS; PREVALENCE; WOMEN